Ecuador : Fourth and Fifth Reviews under the Extended Arrangement under the Extended Fund Facility, Request for a Waiver of Nonobservance of Performance Criterion, Rephasing of Access, and Financing Assurances Review-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Ecuador. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2022)
The economy rebounded more strongly than expected in 2021 at 4.2 percent, bolstered by a well-executed vaccination campaign that allowed for a steady reopening of the economy. The recovery will continue in 2022, but at a more moderate pace of 2.9 percent. Inflationary pressures, mostly due to higher commodity prices, are expected to rise. The government remains committed to the Fund-supported program under the Extended Fund Facility (EFF) of SDR 4,615 million (661 percent of quota, about USD 6.5 billion) that was approved by the IMF Executive Board on September 30, 2020. Upon completion of the combined Fourth and Fifth Reviews under the EFF, an additional SDR 710 million would be made available.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Ecuador